IMPLEMENTATION OF KAIZEN STRATEGY IN IMPROVING HUMAN RESOURCE QUALITY AT TUNAS LUHUR HIGH SCHOOL - Mohammad Syifaur Rizal; Abu Hasan Agur R (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study aims to examine implementation of Kaizen strategy in improvement quality source Power Human resources at Tunas Luhur High School . Kaizen strategy is implemented through five principles main , namely Seiri , Seiton , Seiso , Seiketsu , and Shitsuke , each of which has focuses on continuous improvement in the learning process and school management . The Seiri principle is implemented through the sorting of relevant learning materials and needs-based teacher training. Seiton is realized through the effective arrangement of space and teaching materials, while Seiso emphasizes the cleanliness of the learning environment through exemplary leadership and regular evaluations. The Seiketsu principle is applied through the implementation of standard operating procedures (SOPs) and workshops to maintain learning consistency. Shitsuke is implemented through discipline development and appreciation for teachers who demonstrate professionalism. The results of the study indicate that the synergistic implementation of the five Kaizen principles can improve teacher discipline, professionalism, and the quality of learning. This study concludes that the Kaizen strategy, implemented systematically and sustainably, has a positive impact on human resource development in the school environment.